Graphene intercalated Ni-SiO2/GO-Ni-foam catalyst with enhanced reactivity and heat-transfer for CO2 methanation. (2nd February 2019) - Ma, Haibin; Ma, Kui; Ji, Junyi; Tang, Siyang; Liu, Changjun; Jiang, Wei; Yue, Hairong; Liang, Bin
Graphical abstract: Highlights: A metal-structured Ni-SiO2 /GO-Ni-foam catalyst was synthesized for CO2 methanation. The intercalation of GO on Ni-foam facilitated the formation of stable nickel silicates species. The formed nickel silicates led to a high Ni dispersion and surface OH groups for carbon elimination. DFT calculations revealed the role of graphene on the H2 /CO2 dissociation and CO2 adsorption energy. Heat-transfer confirmed by CFD and stable Ni species resulted in a high stability in CO2 methanation. Abstract: The fabrication of stable Ni active species over the high heat-transfer support is essential for the Ni-based catalysts in CO2 methanation to resist sintering and remove the reaction heat. A metal-structured Ni-SiO2 /GO-Ni-foam catalyst was synthesized via intercalation of graphene oxide (GO) to facilitate the synthesis of stable nickel silicates on Ni-foam, which exhibited excellent activity and stability in the high-temperature (e.g., 470 °C) CO2 methanation. Characterization results suggested that the intercalated graphene over the Ni-foam contributed to a stronger metal-support interaction on the metal-structured catalyst due to the connective function of GO between the Ni-foam and nickel silicates. The formation of nickel silicates on GO lead to high dispersion of Ni sites and high amount of surface OH groups for elimination of carbon deposition. Density functional theory study revealed that the graphene modified the electronic structure of surface Ni, and contributed to an increase of CO2 adsorption energy, Ni4 binding energy with support, and a decrease of H2 and CO2 dissociation energy, and thus led to a high reactivity for CO2 methanation.